Determination of Chicken Meat Suppliers Using the CPI Method - Rinaldi, Muhammad Sam (SEAN Institute, 2023)
In this study the authors conducted research at the Brastagi Medan supermarket in determining chicken meat suppliers. In determining the best supplier of chicken meat, they still do not use a special system so that the determination of suppliers is often inaccurate. To overcome the above, a decision support system application is applied in determining chicken meat suppliers so that suppliers will get rewards in the form of prizes and motivation in entering goods at supermarkets. Another problem that occurs is the recording of valuation data and the calculation of values based on the dimensions set at the Brastagi Medan supermarket decisions in selecting the best chicken meat supplier. The programming languages used to create applications are PHP and MySQL and the method used is the CPI (Composite Performance Index) method. Processing system Selection of the best chicken meat supplier at the Medan Brastagi supermarket is getting better and making it easier to access the system. The purpose of this research is to design a system for selecting the best chicken meat supplier and entering the most goods at the supermarket.